Two opposing theories. On H.E. Wiegand's recent discovery of lexicographic functions - Bergenholtz, Henning; Tarp, Sven (HERMES - Journal of Language and Communication in Business, 2003)
In the history of lexicography, a lot has been said about dictionary users and their needs. This paper will focus on two theories that both share the postulate that dictionaries are tools made by human beings in order to solve specific problems. The first theory is developed by the German scholar H.E. Wiegand and it will be argued that his theory about dictionary use should be considered a linguistic reconstruction of information items in existing dictionaries. The other theory is the modern theory of lexicographic functions that takes all the theoretical and practical consequences of the basic postulate that dictionaries are utility products.